Investigation of microstructure and mechanical properties of friction stir welded AZ61 magnesium alloy joint - Kulwant Singh; Gurbhinder Singh; Harmeet Singh (Journal of Magnesium and Alloys, 2018)
Increasing global demands for energy conservation and environmental protection led to the replacement of heavy components with lighter alloys. As magnesium alloys are believed to be unique candidates for lightweight applications and friction stir welding (FSW) is capable of joining magnesium alloys, in the current work, FSW joint of AZ61 Mg alloy has been fabricated. Microstructure and mechanical properties of the joints were evaluated. The elongated grains of the base metal were recrystallized in the stir zone and in transition zone during friction stir welding. The formation of finer grains in the stir zone of the joint is responsible for increase the hardness of the stir zone. The microhardness of base metal is higher than that of thermo-mechanically affected zone but lower than that of stir zone. The tensile strength of the weld was about 82% of the as-received base metal. The joint failed in ductile mode. This ductile failure of joint was due to the uniform deformation of material. Keywords: Magnesium alloy, Friction stir welding, Stir zone, Microhardness, Microstructure, AZ61